Analyzing volleyball match data from the 2014 World Championships using machine learning techniques - Van Haaren, J.; Ben Shitrit, H.; Davis, J.; Fua, P. (Proceedings of the 22nd ACM SIGKDD International Conference on Knowledge Discovery and Data Mining, 2016)
This paper proposes a relational-learning based approach for discovering strategies in volleyball matches based on optical tracking data. In contrast to most existing methods, our approach permits discovering patterns that account for both spatial (that is, partial configurations of the players on the court) and temporal (that is, the order of events and positions) aspects of the game. We analyze both the men`s and women`s final match from the 2014 FIVB Volleyball World Championships, and are able to identify several interesting and relevant strategies from the matches.